MURINE INVARIANT NATURAL KILLER T CELLS RECOGNIZE GLYCOLIPIDS DERIVED FROM EXTRAC TS OF THE LICHEN Stereocaulon ramulosu - Andrés BAENA (Universidad de Antioquia, 2015)
Background: Invariant natural killer T cells (iNKT ) can be activated by certain types of glycolipids that have the potential to generate adjuvant effects which could be used to develop effective and safe immunotherapies. Many of these glycolipids have been isolated from natural organisms, but there is a great amount of these organisms completely unexplored as a source of these types of compounds. Some of these organisms are lichens which are complex symbiotic organisms that have been showed to contain glycolipids. Objectives: We decide to test if glycolipids isolated from lichens would be able to activate iNKT cells in vitro and in vivo. Methods: We have used extracted glycolipids from 43 different species of lichens from Colombia. We have used iNKT hybridoma cells, C57BL/6 mice, IL-2 ELISA and the B16 melanoma to test for the adjuvant capabilities of glycolipids isolated from lichens. Results: In this study we have found two glycolipids with the capacity to activate iNKT cells in vitro. One of the glycolipids was able to activate iNKT cells in vivo, and was competent to induce protection against the B16 melanoma in the mouse model. Conclusions: We propose a possible chemical structure for a novel glycolipid called β-GalCer-lich (1) derived from the lichen Stereocaulon ramulosum.